The Impact of Project Work and the Writing Process Method on Writing Production - Marcela Díaz Ramírez (Asociación Colombiana de Profesores de Ingles, 2014)
This article presents the outcomes of an investigation whose main goal was to implement the methodology of project work and a process approach in order to improve writing production in an English class of Colombian university students since their diagnostic tests showed that their written production had the lowest score. Based on data collected, four factors were developed in the process of learning to write when project work and the writing process method are implemented: accuracy, fluency, integrative language skills, and a positive perception towards writing.